ISBAT NIKAH SEBAGAI SOLUSI LEGALITAS PERNIKAHAN SIRI: STUDI KASUS DI PENGADILAN AGAMA BINJAI - surbakti, datuk pituah fahmi; Waruwu, Tri Eka Putra M (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
Siri marriages that are not officially registered with the state, even though they are religiously valid, cause various legal, social and administrative problems, especially for women and children. This research aims to examine the factors behind the rampant practice of siri marriage in Binjai City and analyze the effectiveness of isbat nikah as a legality solution within the framework of Islamic law and national law. The approach used is qualitative with a juridical-sociological method through interviews with judges and review of court documents. The results show that local culture, social pressure, economic limitations and low legal literacy are the main factors causing siri marriages. Isbat nikah proved to be an important mechanism to legalize these marriages, but its implementation often faced formal and material obstacles, such as lack of evidence, witness absence, and legal standing issues. Witness istifadah becomes an alternative proof in limited circumstances. This study emphasizes the importance of the active role of judges in maintaining access to justice and the urgency of inclusive legal policies to ensure the protection of the civil rights of siri marriage couples and their children.